A valorização do ser humano e de sua criatividade mediante atividade artesanal com embalagens plásticas: O caso das catadoras de União da Vitória/PR - Sander, Fernanda Perdun; Silva, Denise Abatti Kasper [UNESP]; Baldin, Nelma (My University, 2011)
This article aims to analyze the effects of deploying craftsmanship with PET bottles on the perception of a group of grooming members of the Association of Collectors of the municipality of Union of Victoria - PR in relation to factors such as valuing human life and its potential their creativity and inner strength, social inclusion, self-esteem and record the behavior of the community before the occupation of collector. The basis for this procedure were the methodological principles of qualitative and quantitative research in descriptive mode. Data collection took place through semi-structured interviews and for that the researcher maintained contact with the grooming for six months. It was found from the analysis of the interviews and live with these grooming, the activity in a clean place without exposure to weather and group exercise allowed the creative moments of fun and relaxation and a sense of common family problems. This awareness and the ability to expose their products to others and praise these observers encouraged the self-esteem and gave confidence to grooming. We observed the change in the way of insight about life through health issues facing the personal, professional, family and also financial, as it was possible to extend them the income, albeit modestly.
The recovery of the human being and its creativity by handmade activity with plastic packaging: The case of the União da Vitoria/PR pickers
Keywords: Craftsmanship; Grooming; Social inclusion